Injectable Hydrogels for Localized Cancer Therapy - Fan, Dao-yang; Tian, Yun; Liu, Zhong-jun (Frontiers in Chemistry, 2019)
Traditional intravenous chemotherapy is relative to many systemic side effects, including myelosuppression, liver or kidney dysfunction, and neurotoxicity. As an alternative method, the injectable hydrogel can efficiently avoid these problems by releasing drugs topically at the tumor site. With advantages of localized drug toxicity in the tumor site, proper injectable hydrogel as the drug delivery system has become a research hotspot. Based on different types and stages of cancer, a variety of hydrogel drug delivery systems were developed, including thermosensitive, pH-sensitive, photosensitive, and dual-sensitive hydrogel. In this review, the latest developments of these hydrogels and related drug delivery systems were summarized. In summary, our increasing knowledge of injectable hydrogel for localized cancer therapy is ensuring us it is a more durable and effective approach than traditional chemotherapy. Smart release system reacting to different stimuli at different time according the micro-environment changes in the tumor site is a promising tendency for further studies.